Hubungan Self-Esteem dengan Prokrastinasi Akademik pada Mahasiswa Tingkat Akhir di Universitas Islam Bandung - Maovangi Day, Vania; Rosiana, Dewi (Bandung Conference Series: Psychology Science, 2024)
Abstract. This study aims to look at the relationship between the level of confidence and scientific knowledge of students in a certain year at the Islamic University of Bandung (UNISBA). Procrastination is defined as the activity of delaying or avoiding tasks. While self-esteem is an individual's evaluation of himself, includes both positive and negative things, and describes the extent to which a person's belief in personal abilities, achievements, and self-worth. The measuring instruments used in this study were the Coopersmith Self-Esteem Inventory (CSEI) by Coopersmith, and the Academic Procrastination Scale by Ferrari (1995). The results show that there is a relationship between self-esteem and academic procrastination in final year students at Bandung Islamic University. With a correlation coefficient value of 0.706 which indicates that there is a negative relationship between self-esteem and academic procrastination in final year students at Bandung Islamic University, which means that if self-esteem increases, academic procrastination decreases and vice versa. Abstrak. Penelitian ini bertujuan untuk melihat hubungan antara tingkat kepercayaan dan keilmiahan mahasiswa pada tahun tertentu di Universitas Islam Bandung (UNISBA). Prokrastinasi didefinisikan sebagai kegiatan menunda atau menghindari tugas. Sementara self-esteem merupakan evaluasi individu yang dilakukan terhadap dirinya sendiri, mencakup hal positif dan juga negative, dan menggambarkan sejauh mana keyakinan seseorang akan kemampuan pribadi, pencapainnya, dan nilai dirinya. Alat ukur yang digunakan dalam penelitian ini yaitu, Coopersmith Self-Esteem Inventory (CSEI) oleh Coopersmith, dan skala Prokrastinasi akademik oleh Ferrari (1995). Hasil menunjukkan bahwa adanya hubungan antara self-esteem dengan prokrastinasi akademik pada mahasiswa tingkat akhir di universitas islam bandung. Dengan nilai koefisien korelasi sebesar 0.706 yang menunjukkan bahwa terdapat hubungan korelasi negatif antara self-esteem dengan prokrastinasi akademik pada mahasiswa tingkat akhir di universitas islam bandung yang artinya jika self-esteeem meningkat maka prokrastinasi akademik menurun begitupun sebaliknya.